2023
DOI: 10.1021/acs.jpcb.3c02356
|View full text |Cite
|
Sign up to set email alerts
|

Excluded Volume and Weak Interactions in Crowded Solutions Modulate Conformations and RNA Binding of an Intrinsically Disordered Tail

Abstract: The cellular milieu is a solution crowded with a significant concentration of different components (proteins, nucleic acids, metabolites, etc.). Such a crowded environment affects protein conformations, dynamics, and interactions. Intrinsically disordered proteins and regions are particularly sensitive to these effects. Here, we investigate the impact on an intrinsically disordered tail that flanks a folded domain, the N-terminal domain, and the RNA-binding domain of the SARS-CoV-2 nucleocapsid protein. We mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Though PEG is often used as a mimetic for protein crowders because it is putatively inert, previous studies have reported attractive or repulsive PEG-protein interactions. 28,100 In this section, we investigate in detail the interactions between PEG and mCherry in our simulations. First, we computed the distribution of the number of PEG molecules that mCherry is in contact with throughout the simulations (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Though PEG is often used as a mimetic for protein crowders because it is putatively inert, previous studies have reported attractive or repulsive PEG-protein interactions. 28,100 In this section, we investigate in detail the interactions between PEG and mCherry in our simulations. First, we computed the distribution of the number of PEG molecules that mCherry is in contact with throughout the simulations (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that crowding can lead to either expansion or compaction for IDPs. 7,28 However, IDPs most often experience compaction 9 since the excluded volume effect destabilizes extended conformational states. Several studies have reported that crowding can stabilize helical structures in IDPs, 7,9,20 which has also been attributed to the excluded volume effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding how macromolecules interact in the complex cellular environment is an important but difficult challenge because of crowding effects and weak interactions. Soranno and co-workers use single-molecule FRET under crowded conditions to measure the conformations of an intrinsically disordered protein tail that includes the RNA-binding domain of the SARS-CoV-2 nucleocapsid. They distinguish between the effects of excluded volume screening and weak interactions on the conformational dynamics and binding.…”
Section: The Journal Of Physical Chemistry B: Biophysics Biomaterials...mentioning
confidence: 99%